2021
DOI: 10.1371/journal.pone.0240145
|View full text |Cite
|
Sign up to set email alerts
|

A novel small molecule LLL12B inhibits STAT3 signaling and sensitizes ovarian cancer cell to paclitaxel and cisplatin

Abstract: Ovarian cancer is the fifth most common cause of cancer deaths among American women. Platinum and taxane combination chemotherapy represents the first-line approach for ovarian cancer, but treatment success is often limited by chemoresistance. Therefore, it is necessary to find new drugs to sensitize ovarian cancer cells to chemotherapy. Persistent activation of Signal Transducer and Activator of Transcription 3 (STAT3) signaling plays an important role in oncogenesis. Using a novel approach called advanced mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…We applied a 3-D in vitro ADM model by which primary mouse pancreatic acini dedifferentiate when cultured on the extracellular matrix Matrigel [ 1 ]. We show that a pStat3 inhibitor LLL12B [ 10 , 11 ] and a HDAC inhibitor TSA impede ADM in p48 Cre/+ and p48 Cre/+ ;LSL-Kras G12D/+ (KC) mouse organoids. Furthermore, addition of the compounds to mouse or human tissue cultures after ADM had occurred, resulted in cellular and gene expression changes that suggest a reversal of the dedifferentiated phenotype to one that is more acinar-like.…”
Section: Introductionmentioning
confidence: 99%
“…We applied a 3-D in vitro ADM model by which primary mouse pancreatic acini dedifferentiate when cultured on the extracellular matrix Matrigel [ 1 ]. We show that a pStat3 inhibitor LLL12B [ 10 , 11 ] and a HDAC inhibitor TSA impede ADM in p48 Cre/+ and p48 Cre/+ ;LSL-Kras G12D/+ (KC) mouse organoids. Furthermore, addition of the compounds to mouse or human tissue cultures after ADM had occurred, resulted in cellular and gene expression changes that suggest a reversal of the dedifferentiated phenotype to one that is more acinar-like.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that LLL12B induced apoptosis, suppressed tumor growth, and exhibited synergistic activity in combination with cisplatin or irradiation in medulloblastoma cells [ 25 , 31 ]. In addition, LLL12B sensitized ovarian cancer cells to paclitaxel and cisplatin [ 45 ]. In this study, we evaluated the inhibitory effects of LLL12B on TNBC cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The HIPEC model that was adapted could forecast the bioactive utilisation of cisplatin by regression analysis [ 160 ]. Cisplatin combined with the taxanes is another chemotherapeutic regimen in attenuating OC, but its efficacy is reduced by chemoresistance of the OC cells [ 101 ]. LLL12B is a small molecule inhibitor of chemoresistance that showed improved sensitivity when administered in combination with both cisplatin and paclitaxel together compared to either cisplatin or paclitaxel alone [ 101 ].…”
Section: Recent Advances In Cisplatin-associated Ovarian Cancermentioning
confidence: 99%
“…Cisplatin combined with the taxanes is another chemotherapeutic regimen in attenuating OC, but its efficacy is reduced by chemoresistance of the OC cells [ 101 ]. LLL12B is a small molecule inhibitor of chemoresistance that showed improved sensitivity when administered in combination with both cisplatin and paclitaxel together compared to either cisplatin or paclitaxel alone [ 101 ]. It suppressed cell viability and proliferation by downregulating the signal transducer and activator of transcription-3 (STAT3) pathway [ 101 ].…”
Section: Recent Advances In Cisplatin-associated Ovarian Cancermentioning
confidence: 99%